PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PRAKTEK PELAKU USAHA DI DENPASAR - Br. Surbakti, Putri Febyana; Puspawati, I Gusti Ayu; Rudy, Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013)
The era of globalization and free trade as it is today, many emerging wide range of goods and / or services being marketed to consumers. Food is a commodity that has a high risk because of the food consumed by the public for its survival. But in practice the food product trade shows are still many businesses that knowingly sell food products that have expired, this would be detrimental to consumers because it can endanger the health and safety of consumers. Under the conditions of circulation of food, some problems can be formulated as follows: how regulation on consumer protection against the circulation of expired food and problems faced by consumers in consuming expired food, and how businesses accountability on the circulation of expired food and consumer dispute resolution mechanisms can be taken to resolve the violations. In this case, businesses may be requested accountable in civil, criminal, and administrative state. In the event the dispute can be resolved through the courts or outside the formal court. In addition it is also expected to create dispute resolution that is fast food, simple and cheap so that people are not reluctant to report problems if their rights as consumers have been harmed. In writing this paper used empirical approach juridical and legal materials are processed using qualitative data processing techniques. Furthermore, the data presented in descriptive analysis.
Keywords: consumer protection, food expiry, responsibility, business.